Effect of tool pin profile on corrosion behavior of friction stir processed LM25AA 10% SiCp metal matrix composites. Issue 2 (March 2020) - Senthil, V.; Balasubramanian, E.
Abstract: Friction stir processing (FSP) is a novel technique for microstructure refinement and for the enhancement of surface characteristics of stir casted LM25AA −10% SiCp Metal matrix composite (MMCs) plates. In FSP, a non-consumable tool made-up of harder material plays a critical part in altering the substrate material's surface. In this present work, the influence of various tool pin profiles (Cylindrical straight, taper threaded, threaded cylindrical, square and plain tapered) on the corrosion behavior of friction stir processed (FSPed) LM25AA – 10% SiCp MMCs has been evaluated. The size and dispersion of silicon carbide particles in FSPed MMC were studied and the microstructure, micro hardness, corrosion rate, and the optimum tool pin design to attain desired particle distribution in FSPed MMCs was established. It was found that the decrease of the grain size of the SiC particulates and matrix leads to enhancement of hardness and reduction in corrosion rate.